Effect of dietary crude glycerin on the productive performance of Nile tilapia fingerlings - BALEN,RAFAEL E. (2020)
Abstract The aim of this study was to evaluate the effect of different crude glycerin levels in the diet of Nile tilapia fingerlings (mean initial weight 0.32 ± 0.06 g, n = 450) on growth performance parameters, whole-body composition, blood glucose and liver morphology. Crude glycerin was tested at six different levels (0, 4, 8, 12, 16, and 20%) in diets containing 30% digestible protein and 3,000 kcal kg-1 digestible energy. After 37 days of feeding, the inclusion of crude glycerin resulted in positive effects on final weight, visceral fat, weight gain, feed conversion, specific growth rate and feed intake. The different treatments did not influence fillet yield, glycemia, survival and hepatosomatic index, but intermediate levels of inclusion decreased the area of hepatocytes. Regarding fish body composition, significant differences were found in moisture and ash contents, with no changes in crude protein and total lipid. The inclusion of crude glycerin in the Nile tilapia diet improves growth performance without negatively affecting survival rate and glycemia of fingerlings.